Income or Welfare - Boulding, K. E. (Review of Economic Studies, 1949)
Journal Article Income or Welfare Get access K. E. Boulding K. E. Boulding Ann Arbor, Michigan, U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 2, 1949, Pages 77–86, https://doi.org/10.2307/2295865 Published: 01 January 1949